Efektivitas Metode Ummi dalam Mengembangkan Kemampuan Membaca Al-Qur’an Siswa di Sdit Al-Fikri Islamic Green School Kota Pekanbaru - Yolanda Maya Sari; Wismanto Abu Hasan; Radhiyatul Fithri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Reading the Qur'an with tartil or properly and correctly will not make the person reading it lose, but it will always be a good deed for him. SDIT Al-Fikri Islamic Green School, Pekanbaru City, uses the ummi method in its Al-Qur'an learning process. The method uses a mother tongue approach. The aims of this research are: (1) To find out how the Ummi method is applied in developing the ability to read the Al-Qur'an at SDIT Al-Fikri, (2) To find out how effective the Ummi method is in developing the ability to read the Al-Qur'an at SDIT Al-Fikri, (3) To find out what factors support and hinder the implementation of the ummi method in developing the ability to read the Qur'an at SDIT Al-Fikri. In this research, researchers used qualitative research with a case study approach. Data collection techniques in this research include interviews, observation and documentation. The results of this research are: (1) The implementation of the ummi method at SDIT Al-Fikri has 3 stages, namely: (There is planning, implementation and evaluation of Al-Qur'an learning using the ummi method at SDIT Al-Fikri), (2) After using the ummi method in the Al-Qur'an learning process, SDIT Al-Fikri students experienced development in their ability to read the Al-Qur'an. For more details, see the attachment. (3) The supporting factors in the learning process are: (There is support from foundations, adequate infrastructure and activeness and cooperation from parents). Meanwhile, the inhibiting factor is: teacher change.